Implementasi Nilai Amanah dan Tanggung Jawab Dalam Pendidikan Agama Islam Terhadap Manajemen Kargo dan Distribusi Laut - Prawirosastro, Carlos Lazaro; Saputra, Toto Dwijaya (SENTRI: Jurnal Riset Ilmiah, 2025)
This research is motivated by the widespread ethical violations in the practice of maritime cargo distribution, which reflect a weak integration of moral and spiritual values in maritime logistics management. Therefore, this study aims to analyze the implementation of the values of trustworthiness (amanah) and responsibility in Islamic Religious Education (PAI) as an ethical foundation that can strengthen professionalism and integrity in the management and distribution of maritime cargo. This research employs a descriptive qualitative approach using in-depth interview techniques, participatory observation, and document study to explore the implementation of the values of trustworthiness and responsibility in cargo and maritime distribution management. Informants were selected purposively, and the data were analyzed thematically using the Miles, Huberman & Saldana (2014) model, with validation through triangulation, member checking, and expert discussions. The study concludes that the values of trustworthiness and responsibility taught in Islamic Religious Education have been internalized in the practice of cargo and maritime distribution management through accuracy, honesty, and work discipline. Managerial approaches such as routine evaluations, character training, and reward & punishment systems further reinforce the organizational implementation of these values. Therefore, PAI values deserve to be strategically integrated into the maritime logistics work system as a sustainable moral and professional ethical foundation.